Discriminative EPR detection of NO and HNO by encapsulated nitronyl nitroxides - Bobko, Andrey A. (2012)
Nitric oxide, (•)NO, is one of the most important molecules in the biochemistry of living organisms. By contrast, nitroxyl, NO(−), one-electron reduced analog of (•)NO which exists at physiological conditions in its protonated form, HNO, has been relatively overlooked. Recent data shows that HNO might be produced endogenously and display unique biological effects. However, there is a lack of specific and quantitative methods of detection of endogenous HNO production. Here we present a new method for discriminative (•)NO and HNO detection by nitronyl nitroxides (NNs) using electron paramagnetic resonance (EPR). It was found that NNs react with (•)NO and HNO with similar rate constants of about 10(4) M(−1)s(−1) but yield different products: imino nitroxides and the hydroxylamine of imino nitroxides, correspondingly. An EPR approach for discriminative (•)NO and HNO detection using liposome-encapsulated NNs was developed. The membrane barrier of liposomes protects NNs against reduction in biological systems while is permeable to both analytes, (•)NO and HNO. The sensitivity of this approach for the detection of the rates of (•)NO/HNO generation is about 1 nM/s. The application of encapsulated NNs for real-time discriminative (•)NO/HNO detection might become a valuable tool in nitric oxide related studies.